Musik dalam Pandangan Islam: Studi Pemikiran Ismail Raji Al-Faruqi - Shobrun Jamil (Program Studi Pendidikan Musik FBS UNP, 2022)
This research is to find Ismail Raji Al-Faruqi's view of music. This research is descriptive analytical research with a character study approach, namely Ismail Raji Al-Faruqi. The data is divided into primary and secondary data, the primary data taken is the work of al-Faruqi, namely the Atlas of Islamic Culture and Islamization of Knowledge, secondary data comes from the opinions of Islamic figures related to Islamic science and music. This study concludes that music according to al-Faruqi is part of science in Islam that must be based on monotheism where music that is not in accordance with monotheism should be kept away, because music is a beauty that will ultimately be able to confront obedience to God.